Ketahanan Sosial Masyarakat di Kawasan Rawan Narkotika : Studi Kasus di Kampung Muara Bahari Tanjung Priok Jakarta Utara - Rahmawati, Fika Dewi; Hanita, Margaretha; Iskandar, Anang (UI Scholars Hub, 2021)
In accordance with the mandate of the Narcotics Law Number 35 of 2009, the community has the right and obligation to make efforts to prevent the eradication of narcotics abuse and illicit trafficking (P4GN) in their environment. Through this research, the researcher wants to see how the social resilience of the community in vulnerable areas, especially in Muara Bahari Village, faces the threat of narcotics crime. This research was conducted through a qualitative approach with descriptive analysis. Data were collected through observation and interviews with informants consisting of community leaders, government officials and security forces. It was found that the condition of the people in Muara Bahari Village had economic and social vulnerabilities which then triggered the emergence of narcotics crimes in the area. These conditions make the community also vulnerable to using narcotics and also being involved in the narcotics business. The condition of the social resilience of the people in Muara Bahari Village in general is still weak. Some areas in Muara Bahari Village have started to actively carry out prevention and eradication efforts independently, but some other areas are still passive. This can be seen in the dimensions of social resilience: coping capacity; adaptive capacity; and transformative capacity. Keywords: Narcotics, Narcotics Prone Areas, Narcotics Crime, Organized Crime, Social Security